The DIGITAL FINANCIAL LITERACY PAYMENT APPLICATION AS AN OPTIMIZATION FOR IMPROVING MSME BUSINESS - Gazali; Nurul Alfian; Rohmaniyah; Nilam Ramadhani (KRISNA: Kumpulan Riset Akuntansi, 2026)
Technological developments have brought us to a condition where financial literacy has turned into digital financial literacy (DFL). Research Method In this research, the Prototype method is used because it functions as an initial version of the system. The Prototype method will produce a system as an intermediary between the Developer and the User because it can make it easier for the User to choose a system that suits what is expected. Making a simple software model with a basic depiction used to make the design is the meaning of a prototype. The result of this research is that this application offers various practical features, from bill payments, and money transfers, to online purchases. Apart from that, using the BYLA application can increase ease and efficiency in digital payments which can involve various strategies and innovations aimed at making the payment process faster, safer, and more comfortable for users.